Assessment of Significant Risk Factors in Informal Construction Sector in Tanzania: Workers Perception (The Journal of Building and Land Development, 2024)
The informal construction sector is plagued by risks above other industries due to its features of being unregulated, unlicensed, and unprotected by the state. These features have consequently resulted in failure by the informal construction sector to cope with the existing risk management framework; as a result, significant risk factors facing this sector are not well established. This paper, therefore, examines the significant risk factors based on the likelihood of occurrence and magnitude of impacts in the informal construction sector in Tanzania. A Questionnaire survey was used to collect data and was administered to 1000 artisans working in the informal construction sector in Dar es Salaam and Mwanza. The 1000 artisans were selected through snowball sampling methods. Investigations involved 19 common risk factors which were identified through literature reviews. Statistical methods were used to analyze the data. A quantitative risk analysis result based on the mean value method and risk prioritization number showed that the five top-ranked risk factors with the highest likelihood of occurrence and highest magnitude of impact were lack of safety gears, none or low wages, manual handling, and lack of welfare facilities. These critical significant factors are from health and safety and financial risk categories. Through a one-simple test, the study reveal that all 19 risk factors were significant to the informal construction. It can be concluded that workers in informal construction sectors are vulnerable to many risks which call for putting in place prevention and mitigation strategies to prevent their occurrence and severity. The study recommends improvement in working conditions of workers in the informal construction sector especially of employment contracts  which surface all issues related to  health and safety programme,  payments, welfare facilities and working tools..Keywords:  Informal construction, Risk factors, Risk assessment, Workers